Performance Evaluation of Induced Mutagenesis using Colchicine and EMS Solution on Cowpea M3 Purple and Mung Bean Vima1 to Increase Resistance - I Gede Ketut Susrama; Ni Made Trigunasih; I ketut Suada; Ni Nyoman Ari Mayadewi (Universitas Sebelas Maret, 2022)
Induced mutagenesis is one way to improve the quality of crops, especially to increase the resistance to pests and diseases. This research aimed to determine colchicine and ethyl methane sulfonate (EMS) mutagenesis on cowpea M3 purple and mung bean Vima1, in concatenation for developing resistant crops. This research consists of four packages: (1) first package (cowpea M3 purple seeds treated with colchicine solution, (2) second package (cowpea M3 purple seeds treated with EMS solution), (3) third package (mung bean Vima1 seeds treated with colchicine solution) and (4) fourth package (mung bean Vima1 seeds treated with EMS solution). The results of this research revealed that induced mutagenesis by colchicine solution treatment reduced the incidence of bean leaf beetles up to 19% on cowpea M3 purple, as well leaf miners by 5% to 9% and bean leaf beetles up to 5% on mung bean Vima1. Treatment of EMS solution decreased the incidence of bean leaf beetles by 17% on cowpea M3 purple and pink mealybug by 5% to 15% on mung bean Vima1. Induced mutagenesis using EMS solution significantly decreased vegetable leaf miner incidence by 33% to 93% or 71% on average. Colchicine and EMS solution treatment caused aphid attacks in cowpea M3 purple, particularly in pods. The attacks did not happen on leaves and aphid incidence in pods was slower than in control. Some promising mutant candidates were found from this research that will be used in further crop development studies. It is expected that the method and results of this research could inspire faster development of resistant crops.